Hydrological and hydraulic study of water management system study for PT Bhumireksa Nusasejati, Sumatera, Indonesia - Mustaffar, Mushairry; Katimon, Ayob; Hanapi, Muhammad Nassir; Sa'ari, Radzuan (Faculty of Civil Engineering, 2006)
The hydrology and water management study in Bhumireksa Nusasejati Palm Oil Plantation was commissioned by the Kumpulan Guthrie Bhd. The objective of this study is to evaluate the hydrologic and hydraulic characteristics of the project area in relation to water navigation system of the existing canal. This study involved mainly field and hydrographic survey and investigation that include field data compilation and interpretation and hydraulic modeling exercise.